Recycled glass powder and calcium carbide residue geopolymer to stabilise silty sand soil: Mechanical performances and statistical analysis - Danial Moazami; Meysam Pourabbas Bilondi; Abbas Rahnama; Mojtaba Zaresefat; Laura Moretti (Heliyon)
Geopolymerization is a soil improvement technique widely used for waste management in recent years. This study explores the potential of geopolymerization for roadbed improvement using waste materials. Recycled glass powder (RGP) and calcium carbide residue (CCR) were investigated as precursors and alkaline activators, respectively, to enhance the properties of silty sand soil. X-ray Fluorescence (XRF) analysis confirmed the presence of silicon dioxide in RGP and calcium oxide in CCR. The California Bearing Ratio (CBR) test evaluated the effectiveness of treatments with varying RGP and CCR contents (2–5%) compared to traditional methods (2.5%lime/2.5%cement + RGP). The influence of RGP/CCR content, soaking conditions, and curing time on the stabilised soil was assessed. The geopolymer derived from RGP and CCR significantly improved the load-bearing capacity compared to untreated soil (unsoaked CBR: 85.5 % vs. 45.0 % at 28 days). Notably, soaked CBR increased fourfold after 28 days with the optimal geopolymer content (28.7 % vs. 7.5 %). Statistical analysis confirmed that stabiliser content and sample conditions significantly impacted strength development. These findings demonstrate the effectiveness of geopolymer cement as a sustainable and strengthening alternative for soil treatment, promoting waste utilisation in infrastructure development.